Selection Criteria for Named Subcontractors: Case Study of a Building Project - Hansen, Seng; Fassa, Ferdinand; Michael, Michael (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The execution of construction projects involves many parties, one of which is subcontractors. In general, subcontractors can be divided into three types, namely domestic subcontractors, nominated subcontractors, and named subcontractors. Many studies have been carried out regarding the first two types of subcontractors, but studies related to named subcontractors are scarce. In contrast to nominated subcontractors, named subcontractors are selected by the main contractor based on a list of subcontractor names provided by the employer. This research aims to identify the criteria in selecting named subcontractors by the main contractor. This research applies a qualitative method approach with integrative literature review and interview techniques. The results show the company's experience, financial capabilities, technical capabilities, resource factors, and offer price factors as important selection criteria. This research contributes to the body of knowledge considering that there are still few studies on named subcontractors, especially regarding its selection criteria by the main contractor.